PEMALSUAN SURAT DALAM PEMILUKADA SERENTAK - Ersan, Paramita (Al-Qisth Law Review, 2017)
By enactment of Law No. 8 Year 2015, a new era of Regional Elections have begun, as the Law requires the Indonesian people to hold all Regional Elections simultaneuously. In particular, the most recent Simultaneous Regional Elections was held amidst conflicts of leadership in two major political parties. This gave rise to criminal acts of Letter Forgery in a massive, structurized, and systematical manner throughout the Regional Elections phases. Based on the analysis of Election Oversight Committee (Bawaslu) Decision No. 01/PS/BWSl.Kalteng.21.00/08/2015 and Election Ethics Committee (DKPP) Decision No. 56/DKPP-PKE-IV/2015, there is a challenge in election crime regulations, which must be done quickly with time limit, as mandated by Law No. 8 Year 2015. The human factor that runs the law that is far from ideal, coupled with the dualism within political parties, increases the chance for acts of forgery, which not only resulted in administrative breaches but also have criminal implications. To address this, non-penal approaches would bring more justice and legal order than penal laws. In this regard, a reform is in order, by increasing the knowledge of people involved in the Regional election process. Furthermore, in line with the development of criminal provisions in the Election Law and Penal Code, in practice the integrating approaches is needed between penal and non penal, various related regulations regarding regional elections must also be amended and revised, to accommodate the national political development.